Peningkatan Kapasitas Kader Posyandu Kawasan Pesisir Pangandaran Menuju Generasi Indonesia Merdeka Stunting dan Mandiri Finansial - Akbarsyah, Nora; Thirafi, Luthfi; Khoirunnisa, Khoirunnisa (Unpad Press, 2025)
Stunting causes various problems for children, such as suboptimal intelligence, susceptibility to disease, and low productivity. One area still experiencing these problems is Pangandaran Regency, with a stunting prevalence rate reaching 20% by 2023. This program aims to increase awareness among housewives regarding the importance of fulfilling children's nutrition and good financial management to prevent stunting . The activity was carried out in Kondangjajar Village using a survei and knowledge transfer method. The survei was conducted by interviewing 20 respondents consisting of representatives of cadres from all integrated health posts (Posyandu) in Kondangjajar Village. The activity was divided into several stages: presentations on nutrition and financial literacy, demonstrations of making fish nuggets, and the distribution of cooking equipment to support PMT (Food and Nutritional Supplement) preparations. The survei results showed that most respondents were aged 31-40 years, with the majority of household incomes ranging from Rp. 500,000 to Rp. 1,500,000. Initial results from this activity indicate increased awareness among mothers and integrated health post (Posyandu) cadres regarding the importance of financial literacy in reducing stunting . Furthermore, participants were able to successfully replicate the process of making fish nuggets. Overall, the initial results of this activity indicate a positive reception from participants, as evidenced by the high level of enthusiasm and numerous questions. However, this activity needs to be complemented by ongoing mentoring regarding financial behavior and the provision of assertive communication materials between mothers and children to support daily eating patterns.